Enhancing Knowledge Management Using ICT in Higher Education: An Empirical Assessment - Omona, Walter; Lubega, Jude T.; van der Weide, Theo (Journal of Knowledge Management Practice, 2012)
The main purpose of this paper is to introduce and empirically assess the validity of a proposed conceptual framework for enhancing knowledge management (KM) using ICT in higher education in order to advance strategic goals and direction. The proposed framework delineates the relationships among the key factors that have been identified as integral in enhancing KM using ICT in higher education to arrive at a systematic and holistic framework for improved KM outcomes and consists of higher education process, KM enabling ICT, KM processes and higher education goals. The key dimensions of the proposed framework were tested using case studies of higher education institutions (HEI) in Uganda to examine relative use and effectiveness of the current existing KM enabling ICT tools and technologies; identify key KM processes; and determine critical success factors. The findings provided a confirmatory test of the usefulness of the proposed framework, highlighted indicators which shows that use of KM enabling ICT does not necessarily mean effectiveness, identified key KM success factors, and provided tested inventories of KM enabling ICT and KM processes.